The yeast model system as a tool towards the understanding of apoptosis regulation by sphingolipids. Issue 1 (14th October 2013) - Rego, António; Trindade, Dário; Chaves, Susana R.; Manon, Stéphen; Costa, Vítor; Sousa, Maria João; Côrte‐Real, Manuela
Abstract It has been established that sphingolipids are engaged in the regulation of apoptosis both as direct executors and as signalling molecules. However, the peculiarities of this class of bioactive lipids, namely the interconnectivity of their metabolic pathways, the specific subcellular localization where they are generated and the transport mechanisms involved, introduce a considerably high level of complexity in deciphering their role in the signalling and regulation of programmed cell death. Although yeast is undeniably a simple model, the conservation of the sphingolipid metabolism and of the core machinery engaged in regulated cell death has already provided valuable clues to the understanding of metabolic pathways involved in distinct cellular processes, including apoptosis. It can be anticipated that studies using this model system will further unravel mechanisms underlying the regulation of apoptosis by sphingolipids and contribute to novel therapeutic strategies against serious human diseases associated with dysfunction of sphingolipid‐dependent cell death programmes.